2016
DOI: 10.5194/angeo-34-1197-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of wave energy in the nearshore waters of the central west coast of India

Abstract: Abstract. Assessment of wave power potential at different water depths and time is required for identifying a wave power plant location. This study examines the variation in wave power off the central west coast of India at water depths of 30, 9 and 5 m based on waverider buoy measured wave data. The study shows a significant reduction ( ∼ 10 to 27 %) in wave power at 9 m water depth compared to 30 m and the wave power available at 5 m water depth is 20 to 23 % less than that at 9 m. At 9 m depth, the seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…COV close to zero indicates low variability in wave power and greater than 1.2 is for locations having considerable variability. Minimum values of monthly COV for the locations varied between 0.32 (location 12) and 0.59 (location 13) is observed in January (location 20), February (location 19), April (3)(4)(5)(6)(7)(8)18), June (location 12), and July (location 1,2 and 11). Among 20 locations, the maximum values of COV varied between 0.49 and 1.69.…”
Section: Variations In Monthly Meanmentioning
confidence: 98%
See 1 more Smart Citation
“…COV close to zero indicates low variability in wave power and greater than 1.2 is for locations having considerable variability. Minimum values of monthly COV for the locations varied between 0.32 (location 12) and 0.59 (location 13) is observed in January (location 20), February (location 19), April (3)(4)(5)(6)(7)(8)18), June (location 12), and July (location 1,2 and 11). Among 20 locations, the maximum values of COV varied between 0.49 and 1.69.…”
Section: Variations In Monthly Meanmentioning
confidence: 98%
“…For the BoB locations 13 to 17, low variability in average wave power is observed (small SD~0.19-0.35 kW/m). For the rest of the BoB locations (18)(19)(20), the SD is in the range between 0.51 and 1.81 kW/m. On the other hand, for the AS locations, the SD varied from 0.57 (location 9) to 1.18 kW/m.…”
Section: Variations In Monthly Meanmentioning
confidence: 99%
“…The spatial distribution of total mean wave energy flux and seasonal mean wave energy flux along Indian coast was studied and is found that the west coast of India is more energetic which may be due to the open exposure to swell coming from southern Indian ocean (Patel et al, 2020). Similarly, the variation in wave power off the central west coast of India was examined for different years from 2009 to 2015 at water depths of 30, 9, and 5 m based on the measurement from wave rider buoy (Amrutha and Sanil Kumar, 2016). Wave energy assessment along the Exclusive Economic Zone (EEZ) of India for 39 years using ERA-Interim dataset indicates that the western coast of India adjoining the states of Maharashtra, Goa, Karnataka and Kerala shows an annual average of 10-15 kW/m Wave Power (Haripriya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that site selection for commercial development of wave energy, reduction of grid integration hindrances, and increase of power smoothing are highly dependent on directional exposure of sites. Reference [42] has assessed wave power and its temporal variability for various water depths off the central west coast of India and examined the directional distribution of wave power at shallower water depths. Reference [43] has highlighted the wave (and wind) directionality effects on offshore wind turbines, supported by a jacket structure during hurricane events, while [44,45] have stressed the significance of wave direction, among others, that may lead to larger fatigue damage for certain platforms under specific conditions.…”
Section: Introductionmentioning
confidence: 99%